Understanding the adoption of digital payment in Indonesian SMEs using modified technology acceptance model (Journal of Social Economics Research, 2024)
The purpose of this study is to assess users’ acceptance of OVO (one of the apps that Indonesians frequently use for digital payments) among Indonesian SMEs using a modified version of the technology acceptance model (TAM). A comprehensive investigation is required to understand the factors influencing the acceptability of digital payments in Indonesia, especially in the SME sector. Two hundred and forty-seven SEM actors were subjected to an offline questionnaire. This study adopted a modified technology acceptance model (TAM) with Partial least squares structural equation modeling (PLS-SEM). SmartPLS software is used to evaluate the data. The findings show that the driving force behind the use of digital payments is significantly correlated with its perceived usefulness and security. The influence of these factors on behavioural intention is affected by attitudes towards utilizing. The findings demonstrate the extent to which this digital payment mechanism is relevant and applicable to the majority of SMEs in Indonesia. This study provides information about the key factors that govern users’ consideration to use OVO (as a representation of digital payment apps that are used by SME actors). The intention to adopt digital payment in Indonesian SMEs is high if the user believes that the apps are beneficial and secure.